Screening for Natural Producers Capable of Producing 1,3-Propanediol from Glycerol - Dian Andriani; Wien Kusharyoto; Bambang Prasetya; Thomas Wilke; Klaus Dieter Vorlop (ANNALES BOGORIENSES, 2010)
Glycerol is a renewable resource found as the main  by-product in the transesterification of triglycerides and fat saponification. Due to the increased production of plant oils, especially palm  oil  in developing countries, and their larger use  by the oleochemical industry, glycerol surpluses are on the world market and this may result in a desrease in glycerol  price. As a consequence, biotechnological processes  have been developed to convert this substrate  into  value-added  products,  such  as  1,3-propanediol  (1,3-PD).  The  microbial  production  of  1,3-PD could  be  competitive  to  chemical  routes  assuming  that  it  is  based  on  cheap  raw  material  and  an  optimized process.  In  the  screening  for  1,3  PD–producing  bacteria,  raw  glycerol  as  by-product  from  rapeseed  oil processing unit  was  used  as  a  carbon  source  compared  with  commercial  glycerol.  By  using  increasing concentration of  both  glycerols  from  50  to  150  g/l,  two  potential  bacteria  were  obtained  from  soil  samples.BMP 1 was obtained from an enrichment culture using 50 g/l commercial glycerol, while BMR-1 was obtained from  an enrichment culture using 100 g/l raw glycerol. The highest conversion yield obtained using the isolateBMP-1 was around 0.62 g 1,3-PD formed per  mol glycerol consumed, and 0.73  mol 1,3-PD  formed per  molgycerol using the isolate BMR-1. No bacteria were obtained from cultures using 150 g/l commercial and rawgycerol, respectively, which indicated that higher concentration of glycerol has inhibition effect.   Keywords: 1,3-propanediol, enrichment culture, glycerol, palm oil, screening